Firm Attributes and Corporate Financial Distress of Listed Manufacturing Firms at The Nigeria Exchange Group (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigated the effect of firm attributes on corporate financial distress of listed manufacturing firms in Nigeria. The specific objectives of this study was to investigate the relationship between six dimensions of firm characteristics (profitability, financial leverage, tangibility, liquidity, operating capacity and firms size) and corporate financial distress of manufacturing firms in Nigeria. Ex-post facto research design and a cross sectional time series secondary data covering the period of one hundred and fifty observations (2018-2022) was extracted from the audited financial statement of thrifty (30) manufacturing firms listed on the floor of Nigerian exchange group. The data collected was analysed using descriptive statistics, correlation analysis and Generalized Method of Moments (GMM) of regression analysis. The result from the regression analysis indicated that profitability does positively and significantly affect corporate financial distress; financial leverage does negatively and significantly affect corporate financial distress; tangibility does positively and insignificantly affect corporate financial distress; liquidity does positively and insignificantly affect corporate financial distress; firm size does positively and insignificantly affect corporate financial distress and operating capacity does positively and insignificantly affect corporate financial distress of listed manufacturing firms in Nigeria. Based on the findings, the study generally concluded that firm attributes impact on corporate financial distress of listed manufacturing firms in Nigeria. Hence, it was suggested that corporate managers need to determine and maintain the appropriate level of profitability to ensure smooth operation and continual survival of the organization in term of short run but should be careful in evaluating the long term profitability.